É o tchan do Brasil: história, corpo e erotismo no pagode baiano dos anos 1990 - Lacerda, Gabriela Limeira de (2016)
The starting point of our research is the production of representations on the female body identified in the songs and cultural products by É o Tchan, a pagode band from Bahia. By confronting the images which were built about the body, some issues emerged: how do these representations of the female body obtain such importance inside pagode expressions produced in Bahia in this particular period? What is the importance that such images obtain, particularly those picturing the female body but not only, in the artistic production of É o Tchan? Why is the erotic role played mainly by women? Why were these scenes so usual in the 1990’s? The purpose of this work is to identify the process of making representations of the body in the music through analyzing the particular case of 1990’s pagode from Bahia. The premise is that in this specific case there was an expansion of the mass culture in Brazil. Such expansion reinforced the use of bodies erotically in music, and É o Tchan is its greatest expression. In order to achieve our goal and answer such questions, our work was divided in three parts. In the first one, we propose a debate about the potential links among body, music and history in Brazil. In the next session, we devote our effort to think of the body as a musical brand and the music as a bodily brand, highlighting the role of erotism and the media in this process. In the last part, we focus on É o Tchan case as an example of such practices, which are seen as potentially pedagogic in a analysis of cultural pedagogy. Our main sources are the songs played by the band, TV shows, newspapers and magazines, advertisement and other productions by the group and about the group, specially those released between 1997 and 2000 which were É o Tchan’s most successful years.